Enabling Environment Assessment and Baseline for Scaling Up Handwashing Programs : Peru - Favin, Michael; Alfaro, Doris (World Bank, Washington, DC, 2014)
To follow up country work supported by the Public-Private Partnership for Handwashing, the World Bank Water and Sanitation Program (WSP) received funding from the Bill and Melinda Gates Foundation to support projects to scale up the promotion of handwashing with soap (HWWS) in Peru, Senegal, Tanzania, and Vietnam. The major project objectives of the handwashing Initiative are: (i) inculcate the HWWS habit among millions of mothers and children in these countries; (ii) use a strong monitoring and evaluation (M&E) component to enhance the conceptualizing and management of such programs; and (iii) establish sustainable programs that will continue and expand after this four-year grant ends. Evaluation of actual impact on knowledge, attitudes, and practice regarding HWWS shows some positive and some inconclusive findings. However, the study team feels that much excellent groundwork for the expanded program in Peru has been solidly laid by efforts to date and that, in combination with strong political will from the national government and a certain level of guaranteed funding, the outlook for effective expansion is very good. The Peruvian program implemented activities at the national level and developed partnerships and activities in 14 of Peru's 24 regions. Preliminary monitoring and evaluation showed mixed but promising improvements in knowledge, attitudes, and practices, particularly in handwashing before eating and preparing food. Fostering partnerships at the national, regional, and local levels has been a key project strategy. Although this has been difficult and demanding at times, it has also been a major reason for progress. Both interpersonal communication (in schools and communities) and mass media (mostly print and radio) made important contributions to changing knowledge, attitudes, and practices.